THE EFFECT OF HEALTH EDUCATION BASED ON ANIMATED CARTOON VIDEOS ON THE PREVENTION OF PROP SERUMEN AS A RISK OF CONDUCTIVE DEAFNESS IN STUDENTS IN THE WORK AREA OF THE BULU COMMUNITY HEALTH CENTER - Anjarwati, Dwi; Riyandini, Tiara Putri (jfpublisher, 2025)
Introduction. Cerumen (earwax) can clump and harden to form a cerumen blockage or cerumen prop. This hardening of earwax occurs slowly and over a long period of time, so we often don't realize it. Lumps of earwax (cerumen prop) are only discovered after they cause a disturbing impact in the form of disturbances or complaints to our sense of hearing. Method. This type of research is pre-experimental research using a one group pre-post test design. The population in this study was 54 children with a sample of 48 children under five using simple random sampling. The independent variable in this study is health education based on animated cartoon videos. And the dependent variable is prevention of prop cerumen as a risk of conductive deafness. The instruments in this research were a module outreach program unit and a prop cerumen prevention questionnaire. Result & Analysis. The research results obtained through the Wilcoxon test were p-value 0.000 < -0.05, it can be concluded that H1 was accepted, the difference between the results of preventing prop cerumen with health education based on cartoon animated videos for the pre test and post test. Discussion. This research shows that preventing prop cerumen with health education based on cartoon animation videos has an effect on preventing prop cerumen, shown by almost all students having good knowledge after receiving the intervention compared to before the intervention.